Exploración de la Música Nacional Divulgada en Producciones Audiovisuales Ecuatorianas - Naranjo Alvarado, Luis Alejandro (2023)
Ecuador enjoys a diverse and enriched musical tradition, however, many Ecuadorians are unaware of the various national musical genres and their cultural importance. For this reason, it was considered relevant and necessary to conduct a research on this topic due to the lack of support and scarce diffusion of national music in the country. The main objective of this research was to explore the different national musical genres divulged in the Ecuadorian audiovisual productions included in the streaming platform "Cholo Plus". We took into account the use of mixed and descriptive research, to implement observation sheets, a group approach and an interview that allowed us to know the necessary answers to this problem. Thus, it was concluded that the most used Ecuadorian musical genres in national audiovisual productions are “Pasillo” and “Albazo”. On the other hand, it was found that international genres such as Rock, “Cumbia” and “Salsa” also have greater inclusion in Ecuadorian audiovisual products.